Childhood abuse and cognitive function in a large cohort of middle-aged women - Roberts, Andrea L. (Child maltreatment, 2022)
Cognitive function at middle age is of particular public health interest, as it strongly predicts later dementia. Children who have experienced abuse subsequently have worse cognitive function than those who have not. However, it remains unclear whether the association of abuse with cognitive function persists into middle age. In 2014-2016, 14,151 women ages 49-69 years who had previously responded to a childhood abuse questionnaire completed a cognitive battery. In models adjusted for childhood socioeconomic status and head trauma, combined physical, emotional, and sexual abuse was associated with lower scores on both Learning/Working Memory (severe abuse, lower scores similar to that observed in women 4.8 years older in our data) and Psychomotor Speed/Attention (severe abuse, lower scores similar to that observed in women to 2.9 years older in our data). Adjustment for adulthood socioeconomic status and health factors (e.g., smoking, hypertension) slightly attenuated associations. In exploratory analyses further adjusted for psychological distress, associations were attenuated. Women exposed versus unexposed to childhood abuse had poorer cognitive function at mid-life. Associations were particularly strong for learning and working memory and were not accounted for by adulthood health factors. Childhood abuse should be investigated as a potential risk factor for cognitive decline and dementia in old age.